2019
DOI: 10.1136/bmj.l5367
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and risk of incident acute myocardial infarction and stroke: findings from matched cohort study of 18 million European adults

Abstract: ObjectiveTo estimate the risk of acute myocardial infarction (AMI) or stroke in adults with non-alcoholic fatty liver disease (NAFLD) or non-alcoholic steatohepatitis (NASH).DesignMatched cohort study.SettingPopulation based, electronic primary healthcare databases before 31 December 2015 from four European countries: Italy (n=1 542 672), Netherlands (n=2 225 925), Spain (n=5 488 397), and UK (n=12 695 046).Participants120 795 adults with a recorded diagnosis of NAFLD or NASH and no other liver diseases, match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
183
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(196 citation statements)
references
References 30 publications
(57 reference statements)
7
183
3
3
Order By: Relevance
“…This is in concordance with a meta-analysis of pooled studies from European, Asian, and American countries suggesting an independent association of NAFLD with CV risk [10]. However, a British study including 17.7 million patients found that the diagnosis of NAFLD was not associated with increased risk for acute myocardial infarction or stroke after adjustment for established CV risk factors [22]. Nevertheless, in another meta-analysis of Targher et al, patients with NAFLD evidenced an increased risk of fatal and non-fatal CV disease [23].…”
Section: Discussionsupporting
confidence: 87%
“…This is in concordance with a meta-analysis of pooled studies from European, Asian, and American countries suggesting an independent association of NAFLD with CV risk [10]. However, a British study including 17.7 million patients found that the diagnosis of NAFLD was not associated with increased risk for acute myocardial infarction or stroke after adjustment for established CV risk factors [22]. Nevertheless, in another meta-analysis of Targher et al, patients with NAFLD evidenced an increased risk of fatal and non-fatal CV disease [23].…”
Section: Discussionsupporting
confidence: 87%
“…We acknowledge the heterogenous data in this area and that our study is limited by sample size and follow‐up time, though our cohort had the important strengths of being biopsy‐proven, highly phenotyped and having confirmed clinical end points. While population‐based studies like the one cited have advantages in terms of sample size, they also have limitations, most notably, limited phenotyping, often with a lack of confirmation of diagnosis and endpoints . We similarly believe that larger, multicentre, prospective studies are thus needed to further characterise the relationship between NAFLD and cardiovascular disease and to validate our findings.…”
mentioning
confidence: 79%
“…It should be highlighted that, despite the established knowledge that NAFLD is associated with increased risk for the development of CVD, two recently published large cohort studies provide contradictory results on the monitoring of these patients: one suggests that NAFLD patients should be closely monitored for CVD disease prevention [17], while the other proposes that cardiovascular risk stratification in NAFLD patients should be made in the same way as in the general population [18]. We also know that cardiovascular evaluation is rather conservative for asymptomatic NAFLD patients, based on current recommendations, unless they feature intermediate or high risk or have progressed to NASH cirrhosis [19].…”
Section: Dimitrios Ioannis Patouliasmentioning
confidence: 99%